Jurassic shelf sedimentation and sequence stratigraphy of the Surghar Range, Pakistan (Journal of Nepal Geological Society, 1997)
In the Surghar Range, facies and biostratigraphical analysis of Jurassic deposits show that the platform development was affected by both the variations in sea-level and the influences of a nearby hinterland. The well exposed shallow marine to intertidal sediments of the Shinawari Formation and the Samana Suk Formation were deposited from the Toarcian to the middle Callovian.A rise in sea-level during the lower Toarcian submerged the area which was a delta plain before. Shallowing upward cycles and smaller-scale paracycles are characteristic for the marine sequence. Relative sea-level lowstands occurred during the Bajocian, the Bathonian and the Callovian. The lower two coincide with terrigenous influx from the southeast. A lower Callovian hardground is overlain by transgressive middle Callovian open marine limestones. The Jurassic shallow marine platform development ends with another hardground. Drowning of the platform is indicated by the overlying deeper shelf deposits of the Oxfordian - Neocomian Chichali Formation.